Analisis Sistem Informasi Akuntansi Sebagai Pendukung Pengendalian Internal Pada Larispa Indonesia - Dermawan, Edy; Nst, Murni Dahlena (ARBITRASE: Journal of Economics and Accounting, 2022)
This study aims to find out how the cash in and cash out accounting information systems in companies. This research was conducted at LARISPA (Public Research Institute) Indonesia. This study uses a type of descriptive qualitative research method, with direct observation data and interviews with related parties regarding the company's cash receipts and expenditures. The results showed that the accounting system for cash receipts and expenditures in the company has been implemented systematically by using the Jurnal.id application to record all cash receipts and expenditure transactions, but in the use of the Jurnal.id application, errors were still found in inputting data and network disruptions so that they must be recorded manually until the network stabilizes again.